فاعلية المعاملات الالكترونية في دعم مبدأ الشفافية في قانون 12-23 - اللبي ، زينب (جامعة الوادي University of El Oued, 2025)
يُعد التحول الرقمي اليوم أداة استراتيجية محورية في تعزيز مبادئ الحوكمة الرشيدة وترسيخ الشفافية، وهو ما أقره القانون رقم 23-12 المتعلق بالشفافية والوقاية من الفساد ومكافحته، حيث أكد على أهمية المعاملات الإلكترونية كوسيلة فعالة للحد من مظاهر الفساد وتعزيز الشفافية داخل الإدارة العمومية، لا سيما في مجال الصفقات العمومية. وقد أثبتت المعاملات الإلكترونية نجاعتها في هذا السياق، مما دفع المشرّع إلى تكريسها ضمن الإطار القانوني للقانون 23-12. غير أن نجاح هذا التوجه يظل رهينًا بمدى التزام الدولة بتنفيذه على أرض الواقع، من خلال الاستثمار في البنية الرقمية، وتكوين الكفاءات، وبناء الثقة لدى المواطن في المنظومة الرقمية. Digital transformation is now a pivotal strategic tool for promoting good governance and transparency, as enshrined in Law No. 23-12 on Transparency, Prevention and Combating of Corruption. This law emphasizes the importance of electronic transactions as an effective means of reducing corruption and enhancing transparency within the public administration, particularly in the area of ​​public procurement. Electronic transactions have proven their effectiveness in this context, prompting the legislator to enshrine them within the legal framework of Law No. 23-12. However, the success of this approach remains contingent on the state's commitment to its implementation on the ground, through investment in digital infrastructure, capacity building, and fostering public trust in the digital system.
قانون إداري
Keywords: المعاملات الالكترونية، مبدأ الشفافية، الرقابة; For electronic transactions; the principle of transparency and oversight